LINKING OF REGIONAL AND LOCAL HYDROTHERMAL SYSTEMS IN THE MID-CRUST BY SHEARING AND FAULTING - Oliver N.H.S. (My University, 2001)
The concentration of mass during regional metamorphism and metallogenesis requires interactions between regional and local hydrothermal systems that are scale- and time-dependent. During regional low- to medium-temperature metamorphism in which fluid flow is driven by broad thermal or mechanical gradients, fluid flow rates are (on average) <10-8m/s, and are limited by restricted permeabilities and gentle gradients in hydraulic head. In contrast, coseismic fluid flow rates in major fault zones may reach =<10-2m/s. As a consequence, there may be a limited capacity for individual faults to substantially control fluid flow in the region because of the large contrast in flow rates and permeabilities between faults and low permeability rocks. To produce a major epigenetic ore deposit in overpressured crust, fluid flow systems with such diverse flow rates must interact in such a way that metal dissolution and transport from regional fluid flow systems culminate in focused fluid flow with metal deposition. This is best achieved through two steps; one in which km-scale hydrothermal systems channel into 100m-scale ductile shear zones largely by reaction- and deformation-enhanced permeability in the shear zone; and a second one in which rapid fluid pressure changes accompanying brittle faulting (or intense shearing) within the broader shear zones causes metal deposition and ore genesis.
Keywords: FLUID FLOW; MINERALIZATION; DEFORMATION; PERMEABILITY; SHEAR ZONE; FAULT